NEW DISTRIBUTION RECORD OF Opisthostoma platycephalum (CAENOGASTROPODA: DIPLOMMATINIDAE) FROM PADANG BINDU KARST, SOUTH SUMATRA, INDONESIA - Latifah Nurul Aulia; Reni Ambarwati; Ayu Savitri Nurinsiyah (Treubia, 2024)
A fauna expedition has been conducted in Padang Bindu Karst, South Sumatra in 2021. Among the collected samples, a total of 111 specimens of Opisthostoma platycephalum (Caenogastropoda: Diplommatinidae) were collected from five sampling plots. This discovery is the first record of the land snail species in the southern of Sumatra island, as previous research only recognized its presence in Aceh, North Sumatra, and Peninsular Malaysia. This discovery contributes to the understanding of the biodiversity of South Sumatran land snails and highlights the importance of protecting limestone habitats.